Pollution Evaluation and Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in Water and Coastal Sediment from two Rivers in Douala-Cameroon - Ze Bilo’o Philemon; Mouthe Anombogo Ghislain Arnaud; Jessie Ekoka Christelle Solange; Ngassoum Martin Benoit (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
The authors conducted the present study to expose the level of environmental risk of two rivers through the distribution of PAHs in their water bodies and sediment. The studied rivers are the Mboppi River and the Ngoua River, all in Douala, Cameroon; the first being in a commercial zone, while the second is in an industrial area. Samples of water and sediments were collected during the dry and rainy seasons. The total concentrations of PAHs in sediment from the Ngoua River ranged from 140.42 \(μ\)g.g-1 to 229.47 \(μ\)g.g-1 dry matter in sediment during the rainy season and from 48.89 \(μ\)g.g-1 to 333.49 \(μ\)g.g-1 dry matter in sediment during the dry season. The analysis of the extracts from water samples shows a range of 29.13–461.94 \(μ\)g.L-1 for the total concentration of PAHs in the Ngoua River. All samples showed the predominance of high molecular weight (HMW) PAHs due to industrial activities. Principal component analysis (PCA) also showed remarkable differences in the characteristics of samples collected upstream and downstream of Nettoycam Company along the Ngoua River or Mboppi Market along the Mboppi River, their location, and also of samples from rainy and dry seasons. PAHs of 2 or 3 rings exhibit low concentrations and are even undetectable in certain sediment samples, while they are present in water samples from both rivers. All the studied media (water and sediment) from the studied rivers are all environmentally risky. The toxicity assessment through the determination of the Toxicity Equivalent (TEQ) concentration revealed that.